2006
DOI: 10.1093/bja/ael037
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium moderately decreases remifentanil dosage required for pain management after cardiac surgery

Abstract: Magnesium gluconate moderately reduced the remifentanil consumption without serious side-effects. The opioid-sparing effect of magnesium may be greater at higher pain intensities and with increased dosages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 24 publications
2
16
1
Order By: Relevance
“…Mg could be effective in pain relief by exerting the antinociceptive effect46, inhibiting TNF-α47, and modulating hypesthesia and hyperalgesia4849, by blocking the NMDA receptor. The pain relief effect of Mg has been illustrated by several studies in many cases, such as postoperative sore throat50, tourniquet pain51, major non-laparoscopic gastrointestinal surgery52, diabetic neuropathic pain53, cardiac surgery54, and cancer-related neuropathic pain55. The present study also demonstrated that the single-dose IA Mg was effective in pain relief after arthroscopic surgery.…”
Section: Discussionsupporting
confidence: 70%
“…Mg could be effective in pain relief by exerting the antinociceptive effect46, inhibiting TNF-α47, and modulating hypesthesia and hyperalgesia4849, by blocking the NMDA receptor. The pain relief effect of Mg has been illustrated by several studies in many cases, such as postoperative sore throat50, tourniquet pain51, major non-laparoscopic gastrointestinal surgery52, diabetic neuropathic pain53, cardiac surgery54, and cancer-related neuropathic pain55. The present study also demonstrated that the single-dose IA Mg was effective in pain relief after arthroscopic surgery.…”
Section: Discussionsupporting
confidence: 70%
“…Significant reduction in post‐operative morphine consumption (29.5%) in this study was lower than in gynaecological surgery (40%), as reported by Seyhan et al., who used a comparable administration protocol (40 mg/kg Mg bolus followed by continuous Mg infusion of 10 mg/kg/h) . Steinlechner et al . noted 25% reduction in total post‐operative consumption of remifentanil after cardiac surgery (86.5 mg/kg Mg bolus followed by continuous infusion 13.8 mg/kg/h).…”
Section: Discussionsupporting
confidence: 60%
“…During pre‐operative anaesthesia consultation, patients were clearly informed about the study and educated about PCA use, visual analogue scale (VAS) used to assess pain, the satisfaction scale (0 = complete dissatisfaction and worst discomfort; 100 = best satisfaction and total comfort), and the 3‐point scale for quality of sleep: ‘how well did you sleep last night?’, 1 – very good = sleep all the night, 2 – good = sleep well more than 50% of the night, and 3 – poor = sleep period less than 50%. This sleeping scale was established in our institution, adopted from reported scales and simplified. We allowed patients' parents to help in the assessment of this parameter, as all patients had one of their parents stay with them overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies have reported analgesic effects of systemic administration of MgSO 4 intraoperatively with a resultant reduction of intra‐ and post‐operative opioid requirements during soft tissue surgery, such as hysterectomy or cardiac surgery (Steinlechner et al. ; Ryu et al. ), as well as during orthopaedic surgery (Levaux et al.…”
Section: Introductionmentioning
confidence: 99%